Protein aggregates containing wild-type and mutant NOTCH3 are major drivers of arterial pathology in CADASIL - Nicolas Dupré; Florian Gueniot; Valérie Domenga-Denier; Virginie Dubosclard; Christelle Nilles; David Hill-Eubanks; Christelle Morgenthaler-Roth; Mark T. Nelson; Céline Keime; Lydia Danglot; Anne Joutel (The Journal of Clinical Investigation, 2024)
Loss of arterial smooth muscle cells (SMCs) and abnormal accumulation of the extracellular domain of the NOTCH3 receptor (Notch3ECD) are the 2 core features of CADASIL, a common cerebral small vessel disease caused by highly stereotyped dominant mutations in NOTCH3. Yet the relationship between NOTCH3 receptor activity, Notch3ECD accumulation, and arterial SMC loss has remained elusive, hampering the development of disease-modifying therapies. Using dedicated histopathological and multiscale imaging modalities, we could detect and quantify previously undetectable CADASIL-driven arterial SMC loss in the CNS of mice expressing the archetypal Arg169Cys mutation. We found that arterial pathology was more severe and Notch3ECD accumulation greater in transgenic mice overexpressing the mutation on a wild-type Notch3 background (TgNotch3R169C) than in knockin Notch3R170C/R170C mice expressing this mutation without a wild-type Notch3 copy. Notably, expression of Notch3-regulated genes was essentially unchanged in TgNotch3R169C arteries. We further showed that wild-type Notch3ECD coaggregated with mutant Notch3ECD and that elimination of 1 copy of wild-type Notch3 in TgNotch3R169C was sufficient to attenuate Notch3ECD accumulation and arterial pathology. These findings suggest that Notch3ECD accumulation, involving mutant and wild-type NOTCH3, is a major driver of arterial SMC loss in CADASIL, paving the way for NOTCH3-lowering therapeutic strategies.